Social Integration and the Mental Health of Black Adolescents. Issue 3 (6th November 2013) - Rose, Theda; Joe, Sean; Shields, Joseph; Caldwell, Cleopatra H.
<x xml:space="preserve">Abstract</x> The influence of family, school, and religious social contexts on the mental health of Black adolescents has been understudied. This study used Durkheim's social integration theory to examine these associations in a nationally representative sample of 1, 170 Black adolescents, ages 13–17. Mental health was represented by positive and negative psychosocial well‐being indicators. Results showed that adolescents' integration into family and school were related to better mental health. In addition, commitment to religious involvement positively influenced mental health. Although the direct effect of religious involvement was inversely related to mental health, mediation analyses revealed a positive influence through religious commitment. Findings suggest a greater emphasis on all three social contexts when designing strategies to improve the mental health of Black adolescents.